Crianças e adolescentes atendidos pelo AABB comunidade: histórias de sucesso - (:unkn) unknown (Universidade Federal do Pampa, 2021)
This work aimed to observe the impacts of the AABB Comunidade Program – Bank of Brazil Athletic Association on the life project of children and teenagers assisted in the city of São Borja. The methodology used to approach the problem was the deductive method, which was used in a bibliographic, documental and qualitative analysis research through the reports of the experiences of some subjects participating in the Program. To carry out this study, we used updated data from the 2020 Brazilian Yearbook of Public Security and legal grounds that justify the role of the civil society organization in implementing policies that assist children and adolescents in situations of vulnerability. We studied the specific case of the AABB Community Program and the impact of the action on the life project of children and teenagers assisted by the Program and today, adults. The subjects' voices were extracted from the Program files, through statements collected by the coordinator and did not receive special treatment. We sought an answer to the initial research problem, which was: what did participating in the Program contribute to the development of your life project? We reaffirm that the right to the development of the life project is recognized by the Jurisprudence of the Inter-American Court of Human Rights as a fundamental right that requires the action of the State and society with minimum attention to the basic needs of the subjects of law in training and in situations of vulnerability.
Keywords: Política social; Populações vulneráveis; Política pública; AABB Comunidade; Social policy; Vulnerable populations; CNPQ::CIENCIAS SOCIAIS APLICADAS